2016
DOI: 10.1016/j.ihj.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

CD20 negative B-cell lymphoma presenting as constrictive pericarditis: Rare etiology of acute heart failure

Abstract: We describe a case report of a young girl, who presented with symptoms and signs of acute decompensated heart failure not responding to decongestive therapy. Routine 2D echocardiography revealed a diagnosis of constrictive pericarditis. She underwent pericardiectomy, and etiology of it turned out to be CD20 negative B-cell lymphoblastic primary cardiac lymphoma (PCL). Despite intensive medical and surgical management, it was fatal. PCL is uncommon among cardiac tumors and extremely rare in immunocompetent pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“… 6 Bertog et al studied 163 patients diagnosed with constrictive pericarditis, and lymphoma was the etiology in only two of the patients. 13 In another study, out of eight patients undergoing pericardiectomy for malignant constrictive pericarditis, only one was diagnosed with lymphoma. 14 This unlikeliness has sometimes led to incorrect approaches and treating patients with multiple pericardiocenteses or management according to other diagnoses such as tuberculosis.…”
Section: Discussionmentioning
confidence: 98%
“… 6 Bertog et al studied 163 patients diagnosed with constrictive pericarditis, and lymphoma was the etiology in only two of the patients. 13 In another study, out of eight patients undergoing pericardiectomy for malignant constrictive pericarditis, only one was diagnosed with lymphoma. 14 This unlikeliness has sometimes led to incorrect approaches and treating patients with multiple pericardiocenteses or management according to other diagnoses such as tuberculosis.…”
Section: Discussionmentioning
confidence: 98%
“…It is more common in high-grade lymphomas, particularly double-hit/triple-hit subtypes, and shows a poor prognosis, as in other malignancies (6). Bertog et al studied 163 patients diagnosed with constrictive pericarditis, and lymphoma was the aetiology in only 2 of the patients (9). In another study, out of 8 patients undergoing pericardiectomy for malignant constrictive pericarditis, only one was diagnosed with lymphoma (10).…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial involvement is seen in only 16% of primary cardiac lymphomas, mostly as pericardial effusion and very rarely causing CP [ 7 ]. A study conducted by Bertog et al on 163 patients undergoing pericardiectomy for CP revealed lymphoma as the aetiology in only 2 of the patients [ 3 ]. Buyukbarak et al reported eight cases that underwent pericardiectomy for CP, out of which only one patient had lymphoma [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Constrictive pericarditis (CP) is a rare end stage inflammatory disorder that is characterized by pericardial thickening and the development of dense fibrous adhesions between parietal and visceral pericardium causing myocardial constriction and impaired diastolic filling leading to right heart failure [ 1 , 2 ]. The common causes of CP are idiopathic, prior radiotherapy, renal failure, previous cardiac surgery and infections [ 1 , 3 ]. Malignancy is the least common cause of CP with an incidence of only 4% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%